Microenterprises in developing countries: Is there growth potential? - Helke Seitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Microenterprises account for a large fraction of employment in developing countries and they are likely to increase in importance in the future. In Sub- Saharan Africa, for example, around 8 million additional jobs need to be created annually in order to cope with the increasing number of new entrants into the labour market (The World Bank, 2013). As microenterprises typically only provide subsistence income to few individuals the question remains whether they have the potential to grow and to contribute to the creation of jobs. Studies suggest that many businesses do indeed have the potential to grow. However, they often lack the necessary funds due to imperfect credit markets, insufficient household savings or behavioral reasons and missing information to exploit their potential. Policy interventions to overcome these issues show some promising results.
Keywords: 330